Production of caprine and bovine in vitro-fertilised as well as parthenogenetic embryos and an attempt to vitrify in vivo- and in vitro-derived embryos / Tan Wei Lun - Tan, Wei Lun (2011)
The main objective of this research was to determine the effects of oocyte grading and insemination duration on cleavage rate of embryos obtained from in vitro fertilisation (IVF) in bovine and caprine species. In addition, the effects of oocyte grading in bovine and caprine on production of parthenogenetic embryos as well as an attempt to cryopreserve embryos using vitrification technique were also evaluated. Bovine oocytes were obtained from abattoir while caprine oocytes were retrieved through laparoscopic oocyte pick-up (LOPU) or abattoir source. For laparoscopic oocyte pick-up goats, gonadotrophin injections were involved prior to surgery, which were Estrumate (125 μg), Pregnant Mare’s Serum Gonadotrophin (PMSG) (1500 IU) and Ovidrel (250 IU). Following the washing in Phosphate Buffer Saline (PBS) (for laparoscopic oocyte pickup oocytes) or TL-Hepes medium (for abattoir/ovariectomy oocytes), cumulus oocyte complexes (COCs) were washed with in vitro maturation (IVM) medium. Subsequently, the cumulus oocyte complexes were cultured according to the grades in the droplets of in vitro maturation medium which was pre-incubated overnight in carbon dioxide (5%) incubator at 38.5°C for 18 to 21, 24 to 27 and 22 to 24 hours, for laparoscopic oocyte pick-up caprine oocytes as well as abattoir/ovariectomy caprine oocytes and bovine oocytes, respectively. The grades of oocytes were based on the cumulus layers and the maturation of oocytes was based on the presence of the first polar body. For in vitro fertilisation (IVF), oocytes were partially denuded and co-incubated with post-thawed sperm (1x106 sperm/ml). In vitro culture (IVC) of presumptive zygotes was performed after 8 to 14 or 18 to 24 hours after fertilisation. The fertilisation rate was assessed by the presence of the second polar body. The cleavage rates of the embryos were then observed and recorded. For parthenogenetic activation (PA), matured oocytes were completely denuded and washed with 3 droplets of calcium ionophore, subsequently dimethylaminopyridine (6-DMAP) and incubated in it for 5 hours. After being washed with 3 droplets of preincubated in vitro culture droplets, the oocytes were cultured and the cleavage rates were recorded daily. In an attempt of vitrifying embryos, embryos were placed into holding medium (1 minute), followed by VS1 (3 minutes) and subsequently VS2 (45 seconds) before being plunged into liquid nitrogen. The vitrified embryos were devitrified by being immersed into TS (5 minutes), DS (5 minutes), and finally two holding medium (5 minutes each), stepwise. After being washed thrice in pre-incubated in vitro culture droplets, the oocytes were cultured and the survival rates were recorded daily. The data were analysed by using Analysis of Variance (ANOVA) and Duncan Multiple Range Test (DMRT). In bovine in vitro fertilisation, the maturation rates of Grade A (56.78±6.50%) and Mixed grade (74.69±6.68%) oocytes were significantly (P<0.05) higher than other grades of oocytes (Grades B: 46.58±5.92% and C: 31.29±7.11). The fertilisation rates of Grade A (70.49±6.47%) and Mixed grade (68.18±7.43%) oocytes and the insemination duration of 8 to 14 hours (77.37±6.52%) were significantly (P<0.05) higher. The cleavage rates of Grade A and Mixed grade oocytes were significantly (P<0.05) higher than that of other groups. However, no significant difference (P>0.05) was observed in both insemination durations of 8 to 14 and 18 to 24 hours. In caprine in vitro fertilisation, the maturation rate of Grade A (74.19±5.79%) oocytes was significantly higher than Grades B (54.66±7.42%) and C (42.50±7.20%) oocytes. The fertilisation rate of Grade A oocytes (40.54±8.23%) was significantly higher than that of Grade C (16.26±5.99%) oocytes. The cleavage rates of Grades A (38.39±8.89%) and B (35.90±9.23%) oocytes were significantly higher than Grade C (10.83±5.10%) oocytes; however, no significant differences (P>0.05) were found in the fertilisation and cleavage rates among all grades of oocytes as well as with both insemination durations. In parthenogenetic activation, the cleavage rate of bovine was significantly (P<0.05) higher than that of caprine with the percentages of 63.90±7.30 and 26.77±9.75%, respectively. For the developmental competence of caprine embryos exposed to vitrification solution (toxicity screening) at blastocyst, 75.00% of survival rate for blastocyst up to hatched blastocyst was obtained. The survival rate of 33.33% was achieved in the vitrification of blastocyst. In conclusion, in vitro fertilisation protocols for both bovine and caprine species have been successfully developed, producing satisfactory development of embryos in vitro. However, intrinsic and extrinsic factors (especially those pertaining to specific laboratory situation of a country) that influence the developmental competence of embryos after in vitro fertilisation should be studied in detail, to ensure optimum outcomes of subsequent cleavage, pregnancy and birth.